Testing of a Potentially Used Antiseptic Consists of Povidon Iodine, Hydrogen Peroxide and Aloe Vera - S. Alsaedy, Nabaa; F. Almilly, Raghad; Al-Shannag, Mohammad (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
In this study a new antiseptic was formulated and tested to match the effectiveness against microorganisms. The formulation consisted of Povidone - Iodine (PVP-I) (10%), H2O2 (3%) and Aloe Vera gel (pure). Different ratios of these materials were prepared within the acceptable range of pH for an antiseptic (3-6). The prepared samples were tested. The In Vitro test was performed by using four bacteria, two were Gram-Positive (Staphylococcus aureus and Bacillus cereus) and two were Gram-Negative (Escherichia coli and Pseudomonas aeruginosa). The new antiseptic showed 100% killing rate for E. coli, Ps. aeruginosa and S. aureus and 96.4667% killing rate for B. cereus. When the new antiseptic was compared with two common antiseptics (chloroxylenol (Dettol) and alcohol-based antiseptic), it was superior because the alcoholic antiseptic showed 100% killing rate for E. coli, Ps. aeruginosa and S. aureus and 89.8000% for B. cereus. The Dettol did not show killing rate against bacteria. Ex vivo test was carried out using the sample that showed the highest effectiveness in the In Vitro test. This was performed by applying the formulation on the skin of lab mice after wounding and contaminating the wounds with two bacteria (Staphylococcus aureus and Escherichia coli). After applying the antiseptic on the wounds, swabs from the wounds were taken for testing. The new antiseptic showed amazing efficacy against bacteria by leaving agar dish completely empty from bacteria. In vivo test was also conducted using the polymerase chain reaction (PCR) test for COVID-19. The new antiseptic did not show effectiveness against Coronavirus because the virus could not be isolated like bacteria.